2015
DOI: 10.1177/2322005815607142
|View full text |Cite
|
Sign up to set email alerts
|

Attitude of Students to Clinical Legal Education: A Case Study of Faculty of Law, University of Ibadan

Abstract: The students of the Faculty of Law, University of Ibadan were introduced to the clinical way of legal education in the year 2008. This is a new teaching method different from the traditional method of teaching law. A specialized Women's Law Clinic was also inaugurated to complement the clinical work in the faculty. This article reflects on the attitude of the students to this development, using the results of an unstructured interview of some third-and fifth-year law students, some law graduates and some nonla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…46 There is a consensus that clinical legal education builds self-confidence and improves public speaking skills as the introvert students have been recorded to become bold, assertive and confident. 47 The result of the questionnaire administered to students across Nigeria in the course of this study revealed that 63.5 per cent of the students who participated in this study assert that they are more confident about practising law. Interactions with students that have participated in one form of clinic activity or the other 48 revealed that the students are more assertive in their claims and arguments.…”
Section: Why Clinical Legal Education?mentioning
confidence: 78%
See 2 more Smart Citations
“…46 There is a consensus that clinical legal education builds self-confidence and improves public speaking skills as the introvert students have been recorded to become bold, assertive and confident. 47 The result of the questionnaire administered to students across Nigeria in the course of this study revealed that 63.5 per cent of the students who participated in this study assert that they are more confident about practising law. Interactions with students that have participated in one form of clinic activity or the other 48 revealed that the students are more assertive in their claims and arguments.…”
Section: Why Clinical Legal Education?mentioning
confidence: 78%
“…The teaching system in Nigeria is structured after the English system due to colonization with the teacher-centred approach to teaching on rote learning without emphasis on lawyering skills. 14 During the colonial era in Nigeria, there was no formal training of legal practitioners; rather, persons with basic education and knowledge of the English law were appointed to practise law after being certified as fit and proper to fit in the role as practitioners in Nigeria. 15 These categories of legal practitioners, known as local attorneys, were later joined by practitioners who were trained in Britain as either barristers or solicitors and by 1913, there were about 25 qualified practitioners which led to the end of granting access to unqualified persons to practise law in Nigeria.…”
Section: Clinical Legal Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…21 The clinical legal education stimulates a professional environment of lawyer-client relationship among law students by mixing the theoretical aspects of law with its practical application. 22 Clinical legal education introduced interactive teaching into the law curriculum. It prepares the future lawyers for an inquisitive, informed and active life.…”
Section: Clinical Legal Education Methodsmentioning
confidence: 99%
“…The Network of University Legal Aids Institutions (NULAI), a nongovernmental organization, was established in 2004 primarily to provide supports to the evergrowing network of law clinics in Nigeria (Oke-Samuel, 2008). Since the establishment of law clinics in Nigeria, these clinics have helped in advancing the frontiers of justice, particularly, to the nooks and crannies of Nigeria (Adelakun-Odewale, 2017; Adewumi and Bamgbose, 2016). Access to alternative platform through clinical legal education is important in the sense that access to justice is better enhanced.…”
mentioning
confidence: 99%